Analysis of the Impact of Telemedicine on the Health System in a European Context - Mihaela Mihai; Claudia-Andreea Toma; Daniela-Ioana Manea (Ovidius University Annals: Economic Sciences Series, 2020)
Accessibility, cost, availability and quality of medical services have always been an important topic in the European Union. The rapid development of high-tech technologies, software and hardware, have allowed the emergence of a new trend in the health system, telemedicine. The aim of this paper is to propose a detailed analysis of the openness of the European health system to innovation, in particular to the adoption of telemedicine solutions. Thus, the aim is to identify the barriers of this type of medicine by studying the literature. The application of the analysis in principal components highlights factors that influence the decision of a member state of the European Union to adopt or postpone this trend such as education, level of technology or demographic aspects. The analysis is completed by the study of telemedicine in Romania. The results of the statistical models capture the evolution of telemedicine, offering a general perspective on the spatial impact, emphasizing the specifics of the Romanian health system.